Epidemiological profile of maternal mortality due to postpartum hemorrhage in the state of Paraná in the period from 2012 to 2021 (Research, Society and Development, 2023)
Postpartum hemorrhage is the leading direct cause of maternal mortality worldwide, although numerous causes and triggers can be identified and prevented. The research in question addresses the epidemiological profile of maternal deaths from postpartum hemorrhage in the state of Paraná from 2012 to 2021, as well as comparing the condition of these deaths in relation to Brazil and its regions, especially the South region and its states through the maternal mortality rate. The data was taken from the Mortality Information System (SIM) and the Live Births Information System (SINASC), available on the DataSus/TabNet platform. The data was tabulated in an Excel spreadsheet using percentage calculations and the presentation of graphs and tables. The porpouse of the study is to analyze the situation of the macro-regions, health regions and the age group, race, education level, marital status and place of occurrence of deaths from postpartum hemorrhage in Paraná. It was observed that the South region had the lowest maternal mortality rate among the country's regions and that the state of Paraná had the highest rate in its region. The conclusion is that there are regional disparities in the distribution of deaths, which points to the lack of effective homogeneous obstetric care.